N6-Hydroperoxymethyladenosine: a new intermediate of chemical oxidation of N6-methyladenosine mediated by bicarbonate-activated hydrogen peroxide1. Issue 5 (20th May 2015) - Wu, Jinjun; Xiao, Heng; Wang, Tianlu; Hong, Tingting; Fu, Boshi; Bai, Dongsheng; He, Zhiyong; Peng, Shuang; Xing, Xiwen; Hu, Jianlin; Guo, Pu; Zhou, Xiang
<x xml:space="preserve">Abstract</x> A new route is found in the chemical oxidation of N6-methyladenosine using a H2O2/bicarbonate system through the N6-hydroperoxymethyladenosine (oxm6A) intermediate.